Case Report: Prenatal Diagnosis for a Rett Syndrome Family Caused by a Novel MECP2 Deletion With Heteroduplexes of PCR Product - Zhang, Honghong; Sun, Yixi; Zhu, Yuxia; Hong, Jiali; Zheng, Miaomiao (Frontiers in Pediatrics, 2021)
Rett syndrome is an X-linked dominant, postnatal neurological disorder. Approximately 80%–90% of classic Rett syndrome patients harbor mutations in the coding region of MECP2. Somatic or germline MECP2 mosaicism is not rare, and paternal germline MECP2 mosaicism occurs in especially high proportions. Here, we report the case of a Chinese girl with Rett syndrome in whom a heterozygous deletion was found in exon 4 of MECP2 using multiplex ligation-dependent probe amplification. To obtain an accurate region of deletion, we narrowed down the deletion region using real-time quantitative PCR, and subsequent long-range PCR was performed to detect the deletion breakpoints. Surprisingly, three DNA bands from long-range PCR products were observed after gel electrophoresis. To exclude somatic mosaicism, we performed T-A cloning and DNA sequencing- the middle DNA band was proved to be a heteroduplex of the PCR product. Meanwhile, a prenatal diagnosis was performed for the pregnant mother of the patient. Our study showed that the patient was heterozygous for the deletion of 713-base pairs in exon 4 of MECP2 (MECP2：c.441_1153del713), resulting in a frameshift and premature termination of the 487 amino acid protein at the 154th codon. In summary, we reported a novel heterozygous deletion in the MECP2 gene with heteroduplexes of the PCR product, which can help in the genetic counseling and prenatal diagnosis of disorders of MECP2 defects.